Clinical and electrophysiologic variability in amyotrophic lateral sclerosis within a kindred harboring the C9ORF72 repeat expansion. Issue 2 (March 2013) - Coon, Elizabeth A.; Daube, Jasper R.; Dejesus-Hernandez, Mariely; Adeli, Anahita; Savica, Rodolfo; Parisi, Joseph E.; Dickson, Dennis W.; Josephs, Keith A.; Baker, Matthew C.; Johnson, Kris A.; Ivnik, Robert J.; Petersen, Ronald C.; et al.
Abstract Our objective was to characterize the motor neuron disease features within a large c9FTD/ALS kindred. We analyzed clinical, electrophysiologic and neuropathologic data in a c9FTD/ALS kindred of Scandinavian ancestry. Results showed that of six family members affected, three had only ALS, two had FTD and one had FTD and ALS. Each patient with motor neuron disease had a different clinical presentation: one patient had only bulbar symptoms, one had bulbar and limb involvement, one had limb symptoms, and one had primarily upper motor neuron disease. Later in the course of disease, all ALS patients developed bulbar involvement and died from respiratory causes. Survival was uniformly short (two to five years). Electrophysiologic studies recorded progressive lower motor neuron dysfunction except in the patient with predominantly upper motor neuron features. In conclusion, this kindred demonstrates that the presentation of ALS within c9FTD/ALS families may vary considerably and electrophysiologic findings reflect this heterogeneity.